PELATIHAN LITERASI DIGITAL BERBASIS PEMBELAJARAN KODING DAN ARTIFICIAL INTELLIGENCE (AI) BAGI GURU DI KB DAN RA ICP NURUL ULUM BOJONEGORO - Hamam Burhanuddin; Sri Minarti; M. Jauharul Ma'arif; Rima Dewi Setiani; Luthfiatul Udhma; Isna Mutiara Fajrin (LPPM Institut Pendidikan Nusantara Global, 2026)
This community service activity was motivated by the low level of digital literacy among early childhood education teachers in facing 21st-century learning challenges, particularly in coding and the use of Artificial Intelligence. The activity aimed to improve teachers’ competencies in understanding basic digital literacy concepts, introducing simple coding, and utilizing Artificial Intelligence to support creative classroom learning. The implementation method used a participatory training approach consisting of socialization, workshop practice, mentoring, and evaluation stages. The subjects were 15 teachers from KB and RA ICP Nurul Ulum Bojonegoro. The results showed an increase in teachers’ understanding and skills in using block-based visual coding platforms and Artificial Intelligence applications for developing teaching media. Evaluation results indicated that 85% of participants were able to design simple coding-based learning activities and 80% were able to utilize Artificial Intelligence in preparing digital teaching materials. This activity contributed to improving teachers’ readiness in facing digital transformation in early childhood education.